Reduction of parathyroid hormone with vitamin D supplementation in blacks: a randomized controlled trial. Issue 1 (December 2015) - Chandler, Paulette; Agboola, Foluso; Ng, Kimmie; Scott, Jamil; Drake, Bettina; Bennett, Gary; Chan, Andrew; Hollis, Bruce; Emmons, Karen; Fuchs, Charles; Giovannucci, Edward
Abstract Background Response of parathyroid hormone (PTH) to vitamin D supplementation is determined by the baseline PTH level and change in vitamin D status. Conflicting reports in Blacks exist on the PTH response to vitamin D to supplementation. Methods During 3 winters from 2007 to 2010, 328 healthy Blacks (median age, 51 years) living in Boston, MA were randomized into a 4-arm, double-blind trial for 3 months of placebo, 1000, 2000, or 4000 IU of vitamin D3. PTH was measured in 254 participants at baseline and at the end of vitamin D supplementation period. Results The differences in PTH between baseline and 3 months were 3.93 pg/mL for those receiving placebo, -3.37 pg/mL for those receiving 1000 IU/d, -6.76 pg/mL for those receiving 2000 IU/d, and -8.99 pg/mL for those receiving 4000 IU/d (-2.98 pg/mL for each additional 1000 IU/d of vitamin D3;p < 0.001). Conclusion We found a significant decrease in PTH with increasing doses of vitamin D supplementation up to intakes of 4000 IU/d in Blacks. Trial registration Clinical Trials.gov:NCT00585637